Kinerja Komposit Magnetik Graphene/Tio2/Fe3o4 Dalam Mendegradasi Fenol Dan Pemisahan Hasil Fotodegradasi Fenol - Adharianti, Nia; Heltina, Desi; Aman, Aman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Titanium dioxide (TiO2) is the most widely used material in the photocatalysis process, one of which is to degrade phenol waste. The photocatalysis process can degrading waste compounds become more environmentally friendly compounds, namely CO2 and H2O. To increase the adsorption ability and photocatalysis process efficiency, titanium dioxide was added with carbon-based materials namely graphene. The addition of magnetic materials such as Fe3O4 is expected to facilitate the process of separating photocatalyst with magnetic fields. This research was aims to get graphene/TiO2/Fe3O4 composites for separation of phenol photodegradation results and characterizing graphene/TiO2/Fe3O4 composite. Procedure of this research started with the modification of graphene with cocoPAS surfactant, synthesis of Fe3O4, and synthesis of graphene/TiO2/Fe3O4 composite, performance test of composite using phenol and then magnetic separation test. Morphology of composite graphene/TiO2/Fe3O4 were characterized using SEM analysis. Concentration of phenol photodegradation results were analized using UV-Vis spectrophotometer. The synthesized graphene/TiO2/Fe3O4 composite is successfully in degrading phenol by 57,45 % with the magnetic separation test is 60 minutes.Keywords: photodegradation, magnetic composite, titanium dioxide, graphene, magnetite